2020
DOI: 10.1186/s41938-020-00275-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercropping on the parasitoids, Encarsia spp. and Trichogramma spp. in cotton fields, India

Abstract: Intercropping in cotton is of great significance, which helps to reduce the population of insect pests by attracting natural enemies to the field and helping to get stabilized yield and high profit advantage. The study was conducted with 4 intercrops, viz., sesame, Sesamum indicum L.; pigeonpea, Cajanus cajan L.; pearl millet, Pennisetum glaucum L.; and sorghum, Sorghum bicolor L. in an experimental area during 2016 and 2017 autumn season. The objective was to study the population of parasitoids influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…and Trichogramma spp. were found to be greater in cotton intercropped with pigeonpea or sesame (Devi et al, 2020). Fernandes et al (2018) reported that cotton-cowpea intercropping increased the parasitism of aphids due to the strong attractiveness of predaceous beetles towards cowpea crop (Coleoptera: Coccinellidae).…”
Section: Intrcropping Effectsmentioning
confidence: 99%
“…and Trichogramma spp. were found to be greater in cotton intercropped with pigeonpea or sesame (Devi et al, 2020). Fernandes et al (2018) reported that cotton-cowpea intercropping increased the parasitism of aphids due to the strong attractiveness of predaceous beetles towards cowpea crop (Coleoptera: Coccinellidae).…”
Section: Intrcropping Effectsmentioning
confidence: 99%
“…Recently, the scale Planchonia stentae (Brain, 1920) In addition, species of Cecidomyiidae (Diptera) and mites of the family Phytoseiidae are included as mite predators (unpublished data). The non-exclusivity of the afore mentioned NE species suggests their importance in the regulation of a wide diversity of pests, e.g., T. pretiosum is one of the main species used in inundative BC against lepidopteran pests (Collier and Van Steenwyk 2004;Devi et al 2020).…”
Section: Toward the Complexity Of Agroecosystems: Conservation Of Mul...mentioning
confidence: 99%
“…plantations for many purposes. One of it is to reduce or control the infestation of crop pests such as okra and legumes (Singh et al, 2017), pickerelweed and rice (Xiang et al, 2021) by increasing the population abundance and diversity of parasitoids (Amala and Shivalingaswamy, 2018;Devi et al, 2020), and the second objective is to provide two-in-one crop production (Nchanji et al, 2016;Rocha et al, 2020).…”
Section: P R E S Smentioning
confidence: 99%